2016
DOI: 10.1038/nature17160
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic honesty and the prevalence of rule violations across societies

Abstract: Deception is common in nature and humans are no exception 1 . Modern societies have created institutions to control cheating, but many situations remain where only intrinsic honesty keeps people from cheating and violating rules. Psychological 2 , sociological 3 and economic theories 4 suggest causal pathways about how the prevalence of rule violations in people's social environment such as corruption, tax evasion, or political fraud can compromise individual intrinsic honesty. Here, we present cross-societal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
305
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(360 citation statements)
references
References 33 publications
17
305
1
13
Order By: Relevance
“…20, 21). For example, Gächter and Schulz (22) showed that residents of countries beset with fraud and corruption were more likely than others to cheat in a laboratory task. Moreover, people often project their own history of unethical behavior onto how acceptable they find those acts (23).…”
Section: Significancementioning
confidence: 99%
“…20, 21). For example, Gächter and Schulz (22) showed that residents of countries beset with fraud and corruption were more likely than others to cheat in a laboratory task. Moreover, people often project their own history of unethical behavior onto how acceptable they find those acts (23).…”
Section: Significancementioning
confidence: 99%
“…Despite substantial interest in the origins and determinants of honest behavior in biology (9), behavioral sciences (2, 10), and economics (4,11), little is known about the neural processes that enable humans to resolve conflicts between honesty and personal financial gain. Understanding the neural processes involved in these "costly" displays of honesty could offer important new perspectives on the evolutionary origins and development of honest behavior (9,12) and may also aid in designing interventions for enhancing lie detection (13) and the treatment of pathological cheating (14).…”
mentioning
confidence: 99%
“…honesty | cheating | social decision making | brain stimulation | dorsolateral prefrontal cortex D ishonest behavior is pervasive and carries important economic and societal consequences (1)(2)(3)(4)(5)(6). For example, illegal tax evasion is thought to account for over 5% of the world's gross domestic product (7), and total bribes to public officials are estimated at over US $1 trillion annually (8).…”
mentioning
confidence: 99%
“…For example, rendering (6, 6) too attractive might reduce the likelihood of observing any cross-treatment difference in behavior. Or, recalling that Fischbacher and Föllmi-Heusi (2013), and Gächter and Schulz (2016) found that many people tend to lie but not maximally, rendering a report of 6 too attractive could also render it so suspicious that it would rarely be chosen and coordination would become harder to achieve.…”
Section: Letmentioning
confidence: 99%